Iklim Komunikasi Organisasi Starbucks Bali Discovery Mall - Sitorus, Luke Nicolaf; Alit Suryawati, I Gusti Agung; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
Organization culture had become one of the main factors of Starbucks secret as one of the most successful coffee shop in the world. Kopelman, Brief, and Guzzo tend to agree when they said that organization culture provide a context for climate organization concept. The definition of climate of organizational communication itself means a combination from many perceptions of communication activities such as conflicts among the staff, and a chance for organization growth itself. The purpose of this research is to explain the organization communication climate of Starbucks, as the highest sales rate store in Bali.  This research is using descriptive qualitative technique. The informants were selected by using purposive approach; the data were obtained by doing interview, direct observation, and documentation study. The technique of analyzing data that used in this research through several steps, start from reduction, data display, and conclusion drawing. The result of this research shows the climate of organizational communication of Starbucks Bali Discovery Mall is already positive. It is because researcher found Starbucks Bali Discovery Mall could fulfill all 6 factors of climate of organizational communication. The process of communication top-down, bottom-up, or same level communication were running smoothly. Keywords : Climate of Organizational Communication, Starbucks Bali Discovery Mall.